2015
DOI: 10.1104/pp.15.00437
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Pollen Mitochondrial DNA Copy Number by WHIRLY2: Altered Respiration and Pollen Tube Growth in Arabidopsis

Abstract: In plants, the copy number of the mitochondrial DNA (mtDNA) can be much lower than the number of mitochondria. The biological significance and regulatory mechanisms of this phenomenon remain poorly understood. Here, using the pollen vegetative cell, we examined the role of the Arabidopsis (Arabidopsis thaliana) mtDNA-binding protein WHIRLY2 (AtWHY2). AtWHY2 decreases during pollen development, in parallel with the rapid degradation of mtDNA; to examine the importance of this decrease, we used the pollen vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 67 publications
1
22
0
Order By: Relevance
“…Furthermore, almost 100 genes annotated as encoding proteins involved in mitochondrial transcription were increased significantly in transcript abundance in tric1tric2 plants; however, At2g34620, which is annotated as being involved in the termination of transcription, was down-regulated (Supplemental Table S3). Genes encoding a DNA polymerase (At5g15700) and Whirly2 (At1g71260) also were increased in abundance in tric1tric2 plants, with the latter shown previously to increase mitochondrial DNA copy number when expressed (Cai et al, 2015). Ninety-two genes encoding PPR proteins were significantly differentially expressed in tric1tric2 seedlings, with almost all of these being up-regulated ( Fig.…”
Section: Transcriptome Changes In Tric1tric2 Plants Reveal Direct Andmentioning
confidence: 65%
“…Furthermore, almost 100 genes annotated as encoding proteins involved in mitochondrial transcription were increased significantly in transcript abundance in tric1tric2 plants; however, At2g34620, which is annotated as being involved in the termination of transcription, was down-regulated (Supplemental Table S3). Genes encoding a DNA polymerase (At5g15700) and Whirly2 (At1g71260) also were increased in abundance in tric1tric2 plants, with the latter shown previously to increase mitochondrial DNA copy number when expressed (Cai et al, 2015). Ninety-two genes encoding PPR proteins were significantly differentially expressed in tric1tric2 seedlings, with almost all of these being up-regulated ( Fig.…”
Section: Transcriptome Changes In Tric1tric2 Plants Reveal Direct Andmentioning
confidence: 65%
“…Second, MT (partial fragment of the mitochondrial F1‐ATPase ÎŽâ€Č subunit) (Matsushima et al ., ) was amplified with the primers MT‐ Sal I‐S and MT‐ Nco I‐A (Table S1) from leaf complementary DNA (cDNA) and cloned into pGreen‐ProDD45 via the Sal I and Nco I sites to produce pGreen‐ProDD45‐MT . Finally, GFP–NosT was amplified from pGreen‐WHY2pro : WHY2–GFP (Cai et al ., ) with the primers GFP– Nco I‐S and NosT‐ Sac I‐A (Table S1) and cloned into pGreen‐ProDD45‐MT via the Nco I and Sac I sites to produce pGreen‐ProDD45 : MT–GFP . The vector and pSoup were imported together into Agrobacterium tumefaciens GV3101 by electroporation.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial DNA (mtDNA) is present in many copies per cell, and its levels change during development. For example, the mtDNA levels in somatic cells double before division to ensure that each daughter cell has an mtDNA content similar to that in the mother cell, while the number of mtDNA copies in pollen grains declines from hundreds to dozens during pollen development (Wang et al, 2010;Cai et al, 2015). The mtDNA levels are strictly regulated and closely involved in cellular functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the majority of plant mitochondrial DNA (mtDNA) is inherited from the female. The molecular basis of controlling the maternal inheritance remains largely unexplored (Cai et al, 2015;Zhou et al, 2016). In animals, several recent studies have shown the involvement of autophagy in the mitochondrial inheritance process by removal of paternal mitochondria (Politi et al, 2014;Svoboda et al, 2017;Wei et al, 2017;Palmisano & Mel endez, 2018).…”
Section: Autophagy In Postfertilizationmentioning
confidence: 99%